Effect of Medication Adjustment for Muslim Patients with Uncontrolled Diabetes during Ramadan Period - เจ๊ะยอ นีลนาถ (Journal of Health Science of Thailand, 2021)
The objective of this research was to study the effect of medication adjustment for Muslim patients with uncontrolled diabetes during the period before Ramadan and in Ramadan. The samples were 101 uncontrolled diabetic patients. The study tool was fasting blood sugar monitoring record. The data were analyzed by descriptive statistic, paired t - test and Fisher’s exact test. It was found that our study shows a significant decrease in fasting blood sugar during Ramadan. Patients with hyperglycemia (FBS> 250 mg/dL) were only 1.98%, which was significantly lower than before Ramadan. Therefore, diabetic drug adjustment is useful for Muslim patients with uncontrolled diabetes during the Ramadan period.